Composição e estrutura do estrato regenerativo da mata de galeria inundável da Fazenda Marileuza, Uberlândia/MG - Amorim, Eleonora Henriques (2002)
This study was carried out with objective to know the struture and trees regeneration potential of a fooddable gallery forest. We made a phytossociological inventorie sampling 20 plots of 10 X lOm. The sample included alt individuais height > lm that not included in the canopy stratum (individuais with circunference at breast height (cbh) > 15 cm). Survey recorded 2438 individuais included in 37 species and 37 families, with total density of 12.190ind/ha. The fíve species more important were: Xylopia emarginata (77.34), Miconia chcimissois (39,45), Calophyllum brasiliense (36.14), Protium heptaphyllum (24.02) and Guarea kunthiana (23.03), totaling 66.66% of importance index (IVI). The Shannon & Wienner index (H') found it was 2.14nats/ind, considered low with is low when compared to other at Brazilian forests. A comparison of the present data with a previous canopy layer survey showed that the forest is regenerating, at least partially, with a different composition, because the species presented with higher IVI in the current canopy layer, as: Richeria grandis and Ferdinandusa speciosa, presented low IVI in the regeneration. On the other hand, Síyrax camporum and Guarea kunthiana, common in the present survey apparently assume important position in the future canopy layer. The low floristic diversity of this area reflects the restrictive environmental conditions, above all for the permanently water saturated.